CALL : Revisiting Its Origin, Impact and Challenge - Andy (ELITE JOURNAL, 2023)
Computers have aided language teaching since the 1960s. Two decades after their assistance, with the support of advance in technology and network, computers have gaining trend to be integrated in foreign language teaching as computer-assisted language instruction (CALI). CALI was basically teacher-centered teaching, therefore it was less favoured by the growing belief among educators that teaching should be student-centered. In the early 1980s, with its student-centered approach, computer-assisted language learning (CALL) commenced to substitute CALI. This paper reviews some empirical studies of the impact of CALL as well as its growing trend and challenge. Over the years 1998 –1999, the University of Melbourne held a CALL project. Despite having to tackle students with low computer skill, it was found beneficial not only to tertiary education at the university but also to year 12 students in Victoria. Therefore Australian government started to insert CALL in its curriculum. In 2004, the Ministry of Education of the People's Republic of China also issued policy requiring CALL as means to promote English teaching. Recently, a study supported this policy that it is effective for Chinese students to study EFL writing by utilising Google Translate as a translingual CALL tool. Whilst, in Iran, a study faced challenge of the application of CALL considering limited infrastructure support, teachers’ capability to cope with the technology and apply it in their future instruction. Keywords: CALI, CALL, Australia, China,and Iran